Action figures : men, action films, and contemporary adventure narratives / by Mark Gallagher. - Gallagher, Mark, 1968- (Palgrave Macmillan, 2006)
Action genres have been Hollywood's most profitable global exports for most of its history, their male heroes the subject of much fascination and derision. This book takes stock of action narratives' many appeals and recognizes how crises of gender identity manifest themselves in popular commercial texts.